Managing integration in infrastructure alliance projects: Dynamics of integration mechanisms. Issue 1 (4th January 2017) - Hietajärvi, Anna-Maija; Aaltonen, Kirsi; Haapasalo, Harri
Abstract : Purpose: The effective management of inter-organizational integration is central to complex projects. Such projects pose significant challenges for integration, as organizations struggle with constantly changing inter-organizational interdependencies and must develop and adapt integration mechanisms to meet new demands. The purpose of this paper is to understand what kinds of integration mechanisms are used and how they are developed and adjusted during the infrastructure alliance projects. Design/methodology/approach: This study provides empirical evidence of integration dynamics in project alliancing by analyzing two infrastructure alliance projects – a complex tunnel construction project and a railway renovation project. The research approach is an inductive case study. Findings: This paper identifies integration mechanisms adopted in two case projects and three central triggers that led to changes in the integration mechanisms: project lifecycle phase, unexpected events and project team's learning during the project. Practical implications: Integration capability should be a precondition for alliance project organizations and requires the adoption of a wide range of integration mechanisms, as well as an ability to adjust those mechanisms in response to everyday dynamics and emergent situations. Originality/value: Although unplanned contingencies and the responses to them represent important influences in organizations, there is limited amount of research on the dynamics of integration. The findings will be of value in supporting the management of inter-organizational integration in complex, uncertain and time-critical construction projects.